Nickel–Cobalt Diselenide 3D Mesoporous Nanosheet Networks Supported on Ni Foam: An All‐pH Highly Efficient Integrated Electrocatalyst for Hydrogen Evolution. Issue 19 (6th March 2017) - Liu, Bin; Zhao, Yu‐Fei; Peng, Hui‐Qing; Zhang, Zhen‐Yu; Sit, Chun‐Kit; Yuen, Muk‐Fung; Zhang, Tie‐Rui; Lee, Chun‐Sing; Zhang, Wen‐Jun
Abstract : Novel 3D Ni1− x Co x Se2 mesoporous nanosheet networks with tunable stoichiometry are successfully synthesized on Ni foam (Ni1− x Co x Se2 MNSN/NF with x ranging from 0 to 0.35). The collective effects of special morphological design and electronic structure engineering enable the integrated electrocatalyst to have very high activity for hydrogen evolution reaction (HER) and excellent stability in a wide pH range. Ni0.89 Co0.11 Se2 MNSN/NF is revealed to exhibit an overpotential (η10 ) of 85 mV at −10 mA cm −2 in alkaline medium (pH 14) and η10 of 52 mV in acidic solution (pH 0), which are the best among all selenide‐based electrocatalysts reported thus far. In particular, it is shown for the first time that the catalyst can work efficiently in neutral solution (pH 7) with a record η10 of 82 mV for all noble metal‐free electrocatalysts ever reported. Based on theoretical calculations, it is further verified that the advanced all‐pH HER activity of Ni0.89 Co0.11 Se2 is originated from the enhanced adsorption of both H + and H2 O induced by the substitutional doping of cobalt at an optimal level. It is believed that the present work provides a valuable route for the design and synthesis of inexpensive and efficient all‐pH HER electrocatalysts. Abstract : An integrated electrocatalyst comprising 3D mesoporous Ni0.89 Co0.11 Se2 nanosheet networks on Ni foam is synthesized, and it demonstrates very high activities and excellent stabilities for hydrogen evolution reaction (HER) in all‐pH conditions. Theoretical calculations verify that electronic structure engineering by optimal Co doping enhances the adsorption of H + and H2 O, leading to the advanced all‐pH HER activity of the catalyst.